Novi pogledi na mišično relaksacijo pri endoskopskih posegih - Požar-Lukanovič, Neva (Endoskopska revija, 2011)
Pneumoperitoneum formation during laparoscopic procedures affords good visibility and enough space for surgery. However, it exerts adverse effects onthe patient's respiration and circulation. A special risk is posed by excessive intraabdominal pressure, which may be caused, among other things, byinsufficient relaxation of abdominal wall and diaphragm. Therefore, monitoring of the level of neuromuscular block (NMB) is required. Accelerometry is a clinically appropriate method for NMB monitoring. At the end of the operation, NMB must be reversed in order to prevent serious complications that may result from residual relaxation. Traditional drugs for NMB reversal are inhibitors of enzyme acetyl-choline esterase (AchE), which are relatively inefficient. They are slow acting, cause adverse effects and donot act on deep NMB. A specific ligand of aminosteroid muscular relaxants sugammadex is a promising drug, that reverses NMB immediately, regardless of its depth, and has no adverse side-effects. It allows for appropriate NMB depth required for laparoscopic surgery and minimizes the risk of postoperative residual relaxation.
Keywords: anestezija; laparoskopija; mišična relaksacija